A call to action: dissemination and implementation science education and training is needed in physical therapy and athletic training health professions - de la Motte, Sarah J.; Dartt, Carolyn E.; Root, Hayley J.; Register-Mihalik, Johna; Owoeye, Oluwatoyosi B. A. (Frontiers in Medicine, 2025)
Prevention and appropriate management of musculoskeletal (MSK) conditions is a key contributor to a healthy and well population. Physical therapists (PTs) and athletic trainers (ATs) are allied health professionals at the forefront of prevention and management of MSK conditions, working in wide-ranging healthcare settings, from outpatient clinics, with specialized populations (e.g., athletes), within schools, and in industrial settings and public health. PTs and ATs receive extensive education in evidence-based practice for the prevention and treatment of common MSK conditions, but little to no formal education in dissemination and implementation (D&I) science. This curricular omission may contribute to persistent challenges and gaps in the real-world translation of injury prevention and rehabilitation research into sustainable and effective PT and AT practice. Here the authors, five MSK injury prevention and management researchers and clinicians with experience or expertise in D&I science, present a brief background on the emergence of D&I in the MSK literature, and outline short- and longer-term goals for the integration of D&I into PT and AT education and training, setting forth a vision for the prominence of D&I in the PT/AT professions.